2006
DOI: 10.1530/eje.1.02244
|View full text |Cite
|
Sign up to set email alerts
|

Management of children with idiopathic short stature

Abstract: The Food and Drug Administration (FDA) approved the use of biosynthetic GH for the treatment of children with idiopathic short stature (ISS) in the US in 2003. Primarily, the decision was based on two studies: a randomized placebo-controlled study and a dose-response study, both demonstrating an increase in adult height over the predicted height at baseline and over placebo-treated controls by an average of 4-7 cm. Despite these data and FDA approval of GH treatment for ISS, there is still a significant contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…In 2003, the Food and Drug Administration approved rhGH for children with ISS whose height is more than 2.25 standard deviations (SD) below the mean (or below the 1st percentile). Since the specific etiology for ISS in children is sometimes difficult to identify, children are often diagnosed with ISS and receive growth hormone (GH) therapy [ 3 , 4 ]. TS occurs ~1 in 2,000–2,300 live female births [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…In 2003, the Food and Drug Administration approved rhGH for children with ISS whose height is more than 2.25 standard deviations (SD) below the mean (or below the 1st percentile). Since the specific etiology for ISS in children is sometimes difficult to identify, children are often diagnosed with ISS and receive growth hormone (GH) therapy [ 3 , 4 ]. TS occurs ~1 in 2,000–2,300 live female births [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that all the ISS children patients having normal GH level (Table 1). In comparison to reduced GH rate in patients with endocrine or skeletal diseases, the normal GH pattern is considered to be characteristic for ISS patients (Dunkel, 2006). Nevertheless, measurement of GH level is not easily applicable to clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…GH treatment of ISS was approved in 2003, but such use remains controversial; there is a lack of evidence of psychological or physical morbidity or improved well-being with treatment, cost to the society is high, and the pharmacological dosing JOURNAL 66,67 . There is no reason to expect better growth response with rhIGF-I in these patients than with GH, based on the absence of convincing evidence of GH resistance as a cause of their short stature.…”
Section: Other Indications For Igf-i Therapy For Growth Promotionmentioning
confidence: 97%